Unemployment and mortality in France, 1982-2002 - Buchmueller, Thomas C.; Grignon, Michel.; Jusot, Florence.; Centre for Health Economics and Policy Analysis (Centre for Health Economics and Policy Analysis, McMaster University, 2007)
This study uses aggregate panel data on 96 French departments for the period from 1982 to 2002 to investigate the relationship between macroeconomic conditions and mortality, controlling for local area and time fixed effects. Consistent with research using data from other countries, we find that increases in the local unemployment rates are associated with significant reductions in mortality. Models of mortality by source indicate that the negative relationship between unemployment and mortality is strongest for deaths due to cardiovascular disease and accidents. A finding that mortality among the elderly fluctuates with the unemployment rate suggests the possible importance of externalities associated with economic upturns.
Tom Buchmueller, Michel Grignon, Florence Jusot.
Publisher's website: http://www.chepa.org.
Archived by Library and Archives Canada.
Title from title page of source document (viewed on Jan. 31, 2008).
Keywords: Unemployment; statistics & numerical data; Mortality; Emigrants and Immigrants; Socioeconomic Factors; Economics